Transcranial Magnetic Stimulation as a Diagnostic Tool for Assessing Motor Impairment of Spinal Cord Injured Individuals - Gonzalez, Claudia C. (My University, 2006)
Clinical diagnosis, classification of injury and the reliable and detailed description of a patient's neurological status are key factors in determining intervention, rehabilitation programs and predicting recovery. The American Spinal Injury Association (ASIA) impairment scale (AIS) is a standardized method for spinal cord injury (SCI) classification and neurologic status examination. Studies have revealed the AIS classification to be a general assessment tool that fails to explain the varying degrees and patterns of neurological damage, especially in individuals with incomplete injuries. In addition, intragroup variability can be attributed to inaccuracies in examinations and improper assessment tools that have limited research findings. Transcranial Magnetic Stimulation (TMS) has been used as a non-invasive method of evaluating the integrity of the motor nervous system. The primary purpose of this study was to evaluate TMS as an assessment tool to describe motor impairment of SCI individuals. A second purpose of this study was to assess AIS accuracy and sensitivity to muscle activation by using surface electromyographic (sEMG) techniques during clinical examinations. Six incomplete SCI participants were clinically assessed to obtain their individual motor scores from key muscles following AIS assessment criteria. TMS was then used to stimulate the motor cortex to elicit motor evoked potentials (MEPs) in 4 key muscles. MEPs correlated with motor scores, where significantly higher and lower MEPs corresponded to the highest and lowest motor scores, respectively. Of the 48 muscles analyzed, 18 received a motor score of zero; however MEPs were obtained in 7 of these 18 muscles. In general, MEPs paralleled motor function as assessed by the AIS. Results suggest that TMS may provide information on the relationship between corticospinal integrity and the quality of motor function. In addition, TMS demonstrated adequate validity and sensitivity to SCI individual differences. MEPs provided additional information regarding the existence of spared neuronal pathways not identified by standard clinical evaluations. The therapeutic potential of these motor pathways has yet to be explored. EMG activity was significantly correlated to motor scores and MEPs however; EMG analysis revealed some inaccuracies in muscle examinations and supported MEP data. Results suggest that the implementation of electrophysiological assessment tools may be more sensitive to detect motor damage, adaptive movement patterns and overall muscle activation that may be misinterpreted during clinical examinations.
Keywords: transcranial magnetic stimulation, diagnostic tool, motor impairment, spinal cord injured individuals, rehabilitation, muscles